TosMIC as a Powerful Reagent for Site-Selective α-Formamidomethylation of α-Enolic Dithioesters - Ray, Subhasish; Gupta, Nimisha; Singh, Maya Shankar (Synthesis, 2025)
Herein, we describe a metal-free facile method for the direct synthesis of α-formamidoalkyl-β-ketodithioesters by employing easily accessible α-enolic dithioesters (EDTEs) and p-tosylmethyl isocyanide (TosMIC) via base-mediated cross-detosylative C–C coupling under an open atmosphere. This protocol is mild, operationally simple, highly efficient, and easy to get highly functionalized products in good-to-high yields. A simple mechanism involving Cs2CO3 that promotes highly selective nucleophilic attack of the α-carbon of EDTE to TosMIC followed by hydrolysis is proposed. This efficient approach opens up a new avenue for exploring the synthesis of multifunctional molecules. The carbonyl, dithioester, and amide groups of the products offer a platform for late-stage modification, which could rapidly enrich the structural diversity of the products.
Keywords: Metal-free; α-Enolic dithioesters; TosMIC; Site-selectivity; α-Formamidomethylation